2021
DOI: 10.3390/ijerph181910467
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Experience of Health Extension Workers on Facilitators and Barriers to Maternal and Newborn Health Service Utilization in Ethiopia: A Qualitative Study

Abstract: Background: Health extension workers (HEWs) have substantial inputs to reduce maternal and newborn morbidity and mortality in Ethiopia. However, their perceptions and experiences were not well understood. Therefore, this study aimed to explore their perceptions and experiences on facilitators and barriers to maternal and newborn health services in Ethiopia. Methods: A descriptive qualitative study was conducted from 8–28 April 2021 in Oromia, Amhara and Southern Nation, Nationality, and People’s Regional State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…A study in Sierra Leone also found that maternal education made a considerable contribution to inequalities in institutional delivery [ 16 ]. The cultural aspects of the population as well as their perceptions of modern medicine and related health provision are critical in understanding the use of maternal healthcare services [ 16 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Sierra Leone also found that maternal education made a considerable contribution to inequalities in institutional delivery [ 16 ]. The cultural aspects of the population as well as their perceptions of modern medicine and related health provision are critical in understanding the use of maternal healthcare services [ 16 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Muslim porridge ceremony) prevented many women from wanting to stay in maternity waiting facilities long enough to receive care. 31 Moreover, beliefs about seeking religious support rather than health care support when health issues arose during pregnancy persist. 31 The availability of and relationship between HEWs and the community are another mediator to women receiving PNC.…”
Section: Barriers and Facilitators To Pnc In Ethiopiamentioning
confidence: 99%
“…31 Moreover, beliefs about seeking religious support rather than health care support when health issues arose during pregnancy persist. 31 The availability of and relationship between HEWs and the community are another mediator to women receiving PNC. Differences in expectations sometimes existed for HEW job description and performance.…”
Section: Barriers and Facilitators To Pnc In Ethiopiamentioning
confidence: 99%
“…These services are much more personalized, and users’ network and socioeconomic circumstances are key factors to determine how much demand is required [ 12 , 13 ]. Therefore, considering this in HSC management decisions may improve service impact on social welfare [ 14 ]. For this reason, this research proposes to study how socioeconomic factors and service demand are related.…”
Section: Introductionmentioning
confidence: 99%
“…This study focused on the city of Barcelona and aimed to examine how socioeconomic features are related to the demand for services by means of descriptive analysis at the level of the area of coverage of social service centers (CSSs). Having a better understanding of how people are distributed in the territory according to profiles and needs is an essential tool for developing efficient care strategies [ 14 ]. Many works have focused on home health care [ 19 ] or other types of social care [ 11 ].…”
Section: Introductionmentioning
confidence: 99%